Pengembangan Desain Pengelolaan Metode Mudarosah di Pesantren Tahfidz Bani Yusuf Malang - Gunawan, Satria Amir Makmun (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
In the current era, memorizing the Qur'an is not an easy matter, because humans are busy with their respective activities, making it difficult to prioritize memorization time, and memorization activities are fairly monotonous. This study aims to overcome the problems in managing the mudarosah method at Pesantren Tahfidz Bani Yusuf so that the mudarosah method can run regularly and get maximum results. This research uses a qualitative approach with a case study type of research. Researchers chose observation, interview and documentation techniques in collecting data, then chose purposive sampling techniques in determining informants. The data analysis technique used the Miles and Huberman data analysis model. Researchers used triangulation techniques with the type of source triangulation as a data validity check. The results showed that the concept of developing a management design for the mudarosah method at Pesantren Tahfidz Bani Yusuf consisted of four stages, namely planning, organizing, implementing and controlling/supervising. Supporting factors in the implementation of the mudarosah method, namely the enthusiasm and consistency of the students, the existence of mudarosah supervisors and attendance, a clean recitation place and the role of the management in reminding students. Meanwhile, the inhibiting factors are the students' busyness, memorization partners who are unable to attend and the full capacity of the mudarosah place.